Sufficient Conditions on the Energy to Peak Filter Design for Continuous-Time Polytopic Systems - Acosta-Barbosa, K; El Aiss-Berazouq, H; Zoulagh, T (Institute of Electrical and Electronics Engineers Inc., 2021)
This paper focuses on the L2 - L∞ filtering design problem for polytopic continuous-time systems. In particular, using the parameter-dependent Lyapunov function approach (PDLFA), improved results are obtained based on linear matrix inequality (LMI) formulation. Furthermore, the insertion of the free weighting variables (slacks) approach yields filter design conditions with less conservative outcomes. The main target is to reduce conservatism without raising the number of decision variables. Finally, a numerical example is proposed to show the efficacy of the proposed strategy. © 2021 IEEE.